Investigation of the Ground-State Complex Formation Between Pyrene, Cyanopyrene and Amines by Semiempirical AM1 Method - Acar, Nursel (Asian Journal of Chemistry, 2010)
The aim of the present study is to investigate the intermolecular ground-state complex formation between pyrene (Py), cyanopyrene (CNPy) and amines. Seven different amines have been selected with different but related properties: aliphatic diamines N,N,N',N'-tetramethylethylenediamine (TMED), N,N,N',N'-tetramethyl-1,3-propanediamine (TMPD), N,N,N',N'-tetramethyl-1,4- butanediamine (TMBD); aliphatic cyclic amines 1-azabicyclo-[2.2.2]-octane (ABCO), 1,4- diazabicyclo-[2.2.2]-octane (DABCO) (diamine); dimethyl aniline (DMA) and diethyl aniline (DEA). The complex formation has been investigated by using the AM1 semiempirical method implemented in VAMP module of Accelrys Materials Studio. Heat of formation values, ionization potentials and dipole moments of the studied structures have been calculated for fully optimized structures. Our results have shown that pyrene cannot form amine complexes in the ground state whereas cyanopyrene may form ground-state complexes with the studied aromatic amines dimethyl aniline and diethylaniline. The results have been discussed further in terms of the stability of the investigated systems based on the computed data.